Pengaruh Profitabilitas, Likuiditas, Leverage, Kepemilikan Manajerial, dan Risiko Bisnis Terhadap Kebijakan Dividen dengan Firm Size Sebagai Variabel Moderasi Pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Azizah, Tiara Isny; Paramita, R.A. Sista (Universitas Negeri Surabaya, 2024)
This study aims to examine the effect of probability, liquidity, leverage, managerial ownership, and business risk on dividend policy and to determine whether firm size can moderate the influence of profitability, liquidity, leverage, managerial ownership, and business risk on dividend policy. The sample of this study consisted of 52 companies confirmed by the Indonesian Stock Exchange in the consumer cyclical industry from 2020-2022. The sampling technique used purposive sampling. The analysis technique uses Multiple Regression Analysis (MRA) with STATA 17. The findings obtained show that managerial ownership has a significant positive effect on dividend policy. Profitability, liquidity, leverage, and business risk do not affect dividend policy. Firm size cannot moderate the effect of profitability, liquidity, Leverage, managerial ownership, and business risk on dividend policy. Under the agency model theory, consumer cyclical companies are expected to monitor the performance and the proportion of managerial ownership shares on deciding dividend policy because the more significant the percentage of managerial share ownership will minimise agency conflicts.